Asian infants show preference for own-race but not other-race female faces: the role of infant caregiving arrangements - Liu, Shaoying; Xiao, Naiqi G.; Quinn, Paul C.; Zhu, Dandan; Ge, Liezhong; Pascalis, Olivier; Lee, Kang (Frontiers in Psychology, 2015)
Previous studies have reported that 3- to 4-month-olds show a visual preference for faces of the same gender as their primary caregiver (e.g., Quinn et al., 2002). In addition, this gender preference has been observed for own-race faces, but not for other-race faces (Quinn et al., 2008) However, most of the studies of face gender preference have focused on infants at 3 to 4 months. Development of gender preference in later infancy is still unclear. Moreover, all of these studies were conducted with Caucasian infants from Western countries. It is thus unknown whether a gender preference that is limited to own-race faces can be generalized to infants from other racial groups and different cultures with distinct caregiving practices. The current study investigated the face gender preferences of Asian infants presented with male versus female face pairs from Asian and Caucasian races at 3, 6, and 9 months and the role of caregiving arrangements in eliciting those preferences. The results showed an own-race female face preference in 3- and 6-month-olds, but not in 9-month-olds. Moreover, the downturn in the female face preference correlated with the cumulative male face experience obtained in caregiving practices. In contrast, no gender preference or correlation between gender preference and face experience was found for other-race Caucasian faces at any age. The data indicate that the face gender preference is not specifically rooted in Western cultural caregiving practices. In addition, the race dependency of the effect previously observed for Caucasian infants reared by Caucasian caregivers looking at Caucasian but not Asian faces extends to Asian infants reared by Asian caregivers looking at Asian but not Caucasian faces. The findings also provide additional support for an experiential basis for the gender preference, and in particular suggest that cumulative male face experience plays a role in inducing a downturn in the preference in older infants.